Application of management accounting and business performance: A literature review (International Journal of Scientific Research and Management (IJSRM), 2023)
Research on the application and benefits of management accounting has been carried out by many studies from many developed and developing countries in recent decades. However, there are still limitations to the empirical evidence proving the correlation between management accounting and corporate performance. The study is based on a survey of domestic and foreign scientific documents on the application of management accounting and enterprise performance, through the method of analysis, comparison and synthesis in order to provide an overview of the relationship between management accounting application and enterprise performance. The results show the fact that traditional management accounting is widely used and still brings many benefits. In addition, there is a contradiction that shows the inconsistency in the correlation between the application of management accounting and corporate performance in many studies. In particular, studies on the application of management accounting in Thailand have mostly stopped at identifying the factors affecting the application of management accounting at enterprises but have not evaluated the business results achieved from the application of management accounting.